Assessment the retentive force and XRD analysis on the recycling esthetic thermoplastic acetal clasps - Zwwyer, Rasha Mohammed; Mansoor, Nidhal Sahib (Brazilian Dental Science, 2024)
Objective: To reduce environmental biohazards, technicians should be educated with safe biological waste disposal procedures and dental material recycling. The present study assesses the retentive force, deformation test and XRD analysis of re-injection acetal resin clasps. Material and Methods: specimens were prepared for clasp retention test injection according to the manufacture’s instruction for acetal resin. The first group represent control group with (100% New) and other five groups as experimental groups (group II (25% old +75% new), group III (50% old + 50%) new, and group IV (75% old + 25% new) with different percentages between new acetal materials and old acetal materials, while two last groups with several times (group V (100% old) and group VI (re-injection two times)) only used old acetal materials. The X-ray diffraction (XRD) device used to give structural information for the materials to be tested. The study data were analyzed via One-way ANOVA (LSD) at a significant P-value of (p-<0.05) and a confidence level of 95%. Results: After comparing the results, a significant improvement in the retentive force of acetal clasp specimens after re-injection two times there was found high mean value in group re-injection two times and lower mean value recorded in control group. In XRD patterns of there was no diffraction peak refers to crystal structure of acetal resin. Conclusion: the present study findings concluded that the recycling of acetal resin enhanced the retentive force of acetal clasp and not affected on the crystal structures of material. KEYWORDS Acetal clasp; Esthetic clasp; Recycling; Retentive force; XRD.